The rubbers containing fine elastic fillers - A. E. Kornev; I. M. Agayants; V. G. Nikolskii; I. A. Krasotkina; J. A. Naumova; I. B. Kravchenko (Тонкие химические технологии, 2006)
Influence elastic filler on properties of rubber mixes and vulcanizates is presented